Mechanism of the cooperative Si–H bond activation at Ru–S bonds1. Issue 7 (15th July 2015) - Stahl, Timo; Hrobárik, Peter; Königs, C. David F.; Ohki, Yasuhiro; Tatsumi, Kazuyuki; Kemper, Sebastian; Kaupp, Martin; Klare, Hendrik F. T.; Oestreich, Martin
<x xml:space="preserve">Abstract</x> The heterolytic splitting of hydrosilanes by ruthenium(ii) thiolates is illuminated by a combined spectroscopic, crystallographic, and computational analysis.